Synthetic DNA Vaccines: Improved Vaccine Potency by Electroporation and Co-Delivered Genetic Adjuvants - Flingai, Seleeke; Czerwonko, Matias; Goodman, Jonathan; Kudchodkar, Sagar B.; Muthumani, Kar; Weiner, David B. (Frontiers in Immunology, 2013)
In recent years, DNA vaccines have undergone a number of technological advancements that have incited renewed interest and heightened promise in the field. Two such improvements are the use of genetically engineered cytokine adjuvants and plasmid delivery via in vivo electroporation (EP), the latter of which has been shown to increase antigen delivery by nearly 1000-fold compared to naked DNA plasmid delivery alone. Both strategies, either separately or in combination, have been shown to augment cellular and humoral immune responses in not only mice, but also in large animal models. These promising results, coupled with recent clinical trials that have shown enhanced immune responses in humans, highlight the bright prospects for DNA vaccines to address many human diseases.